Pengaruh Pendidikan Kewirausahaan, Efikasi diri, dan Dukungan Keluarga terhadap Minat Berwirausaha - Astri Fitriani; Yoni Hermawan (Student Scientific Creativity Journal, 2024)
This study is motivated by the phenomenon of rising unemployment rates among SMK graduates. The study is aimed at finding out to what extent entrepreneurial education, self-effectiveness, and family support influence the entrepreneurship interests of students in the 11th grade of the SMKN 1 Marketing in the 2023/2024 academic year both simultaneously and partially. This research uses a survey method with a quantitative approach. Data collection techniques using questionnaires and data analysis techniques using the help of the program SPSS 29.0 for Windows. As for the population in this study, the entire students of class XI of the SMKN 1 Marketing Tasikmalaya school year 2023/2024. The sampling technique in this study is saturated samplings with a total of 122 students. The results of the study show that: 1) There is a significant influence between entrepreneurial education and entrepreneurship interests with a significance value of 0.001 2) There is an significant impact between self-effectiveness and enterprise interest with a signification value of 0.019 3) There is no significant effect between family support for entrepreneur interest with the significance rate of 0.603 4) There are significant influences between enterprise education, self-efficiency, and family support of enterprising interest with an significance of 0.001.